Performance analysis of the Symfony framework for creating modern web application based on selected versions - Wójcik, Aleksander; Wolski, Mateusz; Smołka, Jakub Bartłomiej (Journal of Computer Sciences Institute, 2019)
The subject reached in the article is to check the performance of the Symfony framework for creating web applications. An overview of the literature about Symfony and the most popular modules. Based on the created three identical test applications written in the Symfony 2.8, 3.4 and 4.2 frameworks, they were compared with each other in terms of performance. The test application was written in the blog format. The software architecture style known as the API has been used. Related to this, it is possible to conduct scheduled tests. Symfony’s performance testing for individual versions was based on, the time of loading data from the database and their search in the data collection, additional tests were to download data from a csv file and save them to a csv file.